Kesantunan Berbahasa Pelayan dan Pelanggan di Indomaret (TNSD) Kartasura: Politeness in the Language of Waiters and Pelanggans at Indomaret (TNSD) Kartasura - Fatmawati, Aprilia; Pramesti, Nesgi Septian; Istiqomah, Nurul; Bachtiar, Ryko Muhammad; Putri, Tariska Eka (Kibas Cenderawasih, 2024)
The purpose of this research is to find out and describe the language politeness used by Indomart Kartasura waiters towards customers. The research method used is a descriptive qualitative method, the researcher made direct observations at Indomart Kartasura. The techniques used in qualitative data analysis are divided into four stages of data collection, namely (1) data collection, (2) data reduction, (3) data presentation, and (4) drawing conclusions. In analyzing the research data, the following steps were taken (1) collecting data in the form of conversations; (2) record and sort the data that has been obtained; (3) write down the selected data; (4) describe the data that has been selected, and (5) summarize the results of the analysis. Based on the research carried out, seven data on the principles of language politeness according to Grice were obtained by Indomart waiters. This data, among other things, fulfills the principles of conveying information, requesting information, refusing, expressing feelings, conveying a request, asking for reaffirmation, and saying thank you. This politeness in language occurs because Indomart Kartasura employees are obliged to be friendly towards customers at work.